P412 Time trend in clinicopathological features and prognosis of Ulcerative Colitis associated neoplasia: A nationwide cohort in Japan. (30th January 2023) - Komatsu, K; Shinagawa, T; Noguchi, T; Uchino, M; Ikeuchi, H; Okabayashi, K; Tanaka, S; Futami, K; Itabashi, M; Watanabe, K; Nagahara, H; Okita, Y; et al.
Abstract: Background: With an increase in the number of Ulcerative Colitis (UC) patients in Japan, UC associated neoplasia (UCAN) cases have been accumulated. Laparoscopic surgery for sporadic advanced colorectal cancer was approved in 2002 and biologic agents have been approved for UC from 2010 in Japan. However, few reports have ever examined the time trend using a large patient cohort. We aimed to clarify time trend in clinicopathological features and prognosis of UCAN with a nationwide cohort. This study was conducted as a sub-analysis of the nationwide retrospective study across 47 institutions from the Japanese Society for Cancer of the Colon and Rectum. Methods: A total of 1, 139 UCAN patients were identified in the nationwide cohort from 1983 to 2020. Clinicopathological features, 5-year cancer specific survival (CSS) and overall survival (OS) were compared among the following three groups by the period of UCAN diagnosis, before 2000, 2001-2010 and 2011-2020 (the results are shown in this order). Results: The number of UCAN patients registered in the database were 59, 340 and 740 in each period. Age at UCAN diagnosis (47, 51, 54, median, p<0.01) and the disease duration from UC diagnosis to UCAN diagnosis (14.3, 16.0, 17.5 years, mean, p<0.01) increased through the study periods. The rate of a surveillance colonoscopy as a diagnostic procedure (36.2%, 58.6%, 72.8%, p<0.01) increased without a change in the ratios of early (pathological stage 0-I) neoplasia (60.7%, 59.5%, 62.2%, p=0.72). Laparoscopic surgery became a dominant surgical procedure in the recent cases (1.7%, 33.2%, 47.7%, p<0.01) without an increase in postoperative complication rate (39.7%, 29.2%, 29.8%, p=0.26). Improvement in 5-year CSS (77.2%, 87.5%, 90.7%, p<0.05) and OS (77.2%, 84.3%, 88.5%, p<0.05) was observed. Among pathological stage III patients, better curative resection rate (66.7%, 92.6%, 97.1%, p<0.01) and the more use of adjuvant chemotherapy in the last decade (50.0%, 58.5%, 76.6%, p<0.05) were observed. Conclusion: Longer duration of UC before the diagnosis of UCAN was observed in recent cases, which might be due to the improvement of medical therapy, including biologic agents. Minimally invasive surgery prevailed without an increase in postoperative complications. Curative resection and adjuvant chemotherapy might play a role in improvement of 5-year CSS and OS.